Effect of Current Density on the Dynamical Evolution of Liquid Water Distribution within the Gas Diffusion Layers of PEMFC Employing a Multi-Timescale Kinetic Monte Carlo Method. Issue 4 (9th March 2019) - Pournemat, A.; Wilhelm, F.; Scholta, J.
Abstract : The liquid water produced in the cathode reaction layer of a polymer electrolyte membrane fuel cell (PEMFC) can obstruct the transport paths of the reactant gases within the gas diffusion layers (GDL), especially at high current densities. This may lead to fuel starvation, reduced overall cell performance and lifetime. In this study, using a newly developed multi-timescale kinetic Monte Carlo model, the evolution of the liquid water distribution over time within a real GDL structure for different current densities is simulated. The processes included in this model comprise water transport and water generation, which occur on two different timescales. The multi-timescale model allows for sampling both process types by implementing the much slower water production reaction with a defined interval among the faster and more frequent water movement steps. The simulation results reveal how the real cell operating conditions and GDL surface wetting properties can affect the amount and distribution of liquid water clusters within the structure.